JURIDICAL REVIEW OF CHANGES TO THE DECISION OF THE CONSTITUTIONAL COURT IN THE 2024 GENERAL ELECTION CONTESTATION REVIEWED FROM THE PERSPECTIVE OF INDONESIAN CONSTITUTIONAL LAW - Agoes Djatmiko; Elisabeth Pudyastiwi; Elly Kristiani Purwendah (Ganesha Law Review, 2024)
This article aims to analyze changes to the decision of the constitutional court in the 2024 general election contestation from the perspective of Indonesian constitutional law. This research uses a normative juridical research method with a type of approach, namely a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials, obtained by conducting literature studies. The research results show that factors that influence changes in the Constitutional Court's decisions will be taken into account, such as legal developments, social changes and political shifts that may occur over time. Through a review of constitutional law, this article will also consider the influence of constitutionalist thinking and human rights principles in the Constitutional Court's decisions regarding elections. This research pays attention to changes in the constitutional interpretation by the Constitutional Court and their impact on the electoral process.